2022
DOI: 10.2298/tsci210920011d
|View full text |Cite
|
Sign up to set email alerts
|

A novel vortex combustion device: Experiments and numerical simulations with emphasis on the combustion process and NOx emissions

Abstract: Experimental and numerical studies of combustion process in a vortex flow device have been developed. The modelling part of the study has been performed by means of ANSYS Fluent package. Fuel droplet trajectories and the flow pattern on their motions have been modeled by the function ?injection?. The combustion process utilized the k-? turbulence model. A special trend on the effect of the vortex generator blade orientation on the gross process has been developed. It has been established that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous studies of combustion processes have shown that the turbulence model has a sufficient level of accuracy [15], which determined the choice of this model.…”
Section: Numerical Model and Verificationmentioning
confidence: 99%
“…Previous studies of combustion processes have shown that the turbulence model has a sufficient level of accuracy [15], which determined the choice of this model.…”
Section: Numerical Model and Verificationmentioning
confidence: 99%